A Traveller in War-Time - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Traveller in War-Time" by Winston Churchill is a collection of observations and reflections written during World War I, likely in the late 1910s. The text offers insights into the experiences of a visitor traversing war-affected landscapes in Britain and France, capturing the atmosphere of a world under siege. Churchill aims to convey the realities faced by both soldiers and civilians while exploring themes of human resilience, social change, and the spirit of patriotism amid hardship. The opening of the work begins with Churchill's preface, where he outlines his intention to share his vivid impressions of Britain and France during wartime, emphasizing the pursuit of authenticity in his observations. As he travels aboard a crowded ship from New York to Europe, he notes the diverse range of American individuals enlisting and their willingness to sacrifice comfort for the greater good. Through richly descriptive passageways from the ship to his arrival in France, Churchill details interactions with fellow passengers$1 (Bfrom Red Cross workers to soldiers$1 (Bexpressing a collective determination to aid in the war effort. His accounts serve as a reflective lens on the social transformations prompted by war, highlighting the newfound purpose of individuals across American society. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Traveller_in_War-Time
Release date is 2004-10-19
Produced by David Widger
Keywords: World War, 1914-1918 -- Personal narratives